Podziały etniczne i narodowościowe w Republice Mołdawskiej. Wpływ i znaczenie edukacji w dwóch odrębnych państwach – Gagauzji i Naddniestrzu - Kasprzak, Tomasz (Wydział Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
Moldova is a country of many paradoxes. three state capitals, located on the territory of the historical Bessarabia. I wanted to conclude the problem of Moldova's national identity and its impact on education today, especially in the autonomous territories: Gagauzia and Transnistria. Moldova is split between: the East – growing power of Russia with her influence in Transnistria and the West – the European Union and Romania. Therefore, the issue of education in Moldova is due to bilingualism and dual citizenship. Lack of an official language makes it difficult to make reforms in education. Moldova in education, is trying to emphasize the uniqueness of national and ethnic.
Ethnic and National Divisions in the Republic of Moldova. The Impact and Significance of Education in the Two Separate States – Gagauzia and Transnistria
Keywords: nationality; ethnicity; autonomy; education; the importance